2013
DOI: 10.1111/risa.12093
|View full text |Cite
|
Sign up to set email alerts
|

Systems Resilience for Multihazard Environments: Definition, Metrics, and Valuation for Decision Making

Abstract: The United Nations Office for Disaster Risk Reduction reported that the 2011 natural disasters, including the earthquake and tsunami that struck Japan, resulted in $366 billion in direct damages and 29,782 fatalities worldwide. Storms and floods accounted for up to 70% of the 302 natural disasters worldwide in 2011, with earthquakes producing the greatest number of fatalities. Average annual losses in the United States amount to about $55 billion. Enhancing community and system resilience could lead to massive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
261
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 458 publications
(268 citation statements)
references
References 34 publications
(41 reference statements)
1
261
0
6
Order By: Relevance
“…This definition is very similar to the definition proposed by Ayyub [Ayyub, 2013], but it is more explicit in that it specifically calls out the fact that an estimate of resilience depends on the set of disturbances over which it is valid, as well as the fact that it exists within an operational timeframe.…”
Section: Resilience Ismentioning
confidence: 85%
See 1 more Smart Citation
“…This definition is very similar to the definition proposed by Ayyub [Ayyub, 2013], but it is more explicit in that it specifically calls out the fact that an estimate of resilience depends on the set of disturbances over which it is valid, as well as the fact that it exists within an operational timeframe.…”
Section: Resilience Ismentioning
confidence: 85%
“…This last argument is reinforced by the fact that the probabilistic nature of inputs and outputs warrants the consideration of a probabilistic measurement of mission risk [Haimes, 2009] [Holling, 1993]. Ayyub defined resilience in multi-hazard environments as "the persistence under uncertainty of a system's performance in the face of disturbances" [Ayyub, 2013]. Together, Holling and Ayyub indicate the importance of needing multiple contextual attributes to support the development of resilience metrics.…”
Section: Comparison With Previous Work and Definitionsmentioning
confidence: 99%
“…Vugrin et al (2010) defined resilience as the ability of a system to efficiently reduce both the magnitude and duration of the deviation of system performance from the targeted system performance levels. Ayyub (2014) mentioned resilience as the ability of the system to return to a stable state after a perturbation. Based on the concepts of Bruneau et al (2003), various dynamic measures were reported for assessing the system's ability to bounce back from a failure state, as seen above.…”
Section: Introductionmentioning
confidence: 99%
“…First, the design principles described here are based upon static rather than dynamic measures of resilience. Although many authors have identified the need for such dynamic measures, the literature has yet to produce them [7,9,10,32,45,64,76,90,95]. Therefore, it is likely that the design principles described here will be expanded as the system resilience literature develops further.…”
Section: Design Principles For a Change Of System Dynamicsmentioning
confidence: 99%